Effectiveness of pre-procedural rinsing with essential oils-based mouthrinse to reduce aerosol contamination of periodontitis patients - A.S. Sadun,; T.B. Taiyeb-Ali,; Fathilah A.R.,; Himratul-Aznita W.H.,; R. Saub,; S.H. Safii,; Z.A. Che Ab Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This research aims to evaluate the effectiveness of pre-procedural rinsing using essential oils-mouthwash (Listerine®) in reducing bioaerosol contamination in a dental clinic. Thirty (30) subjects who consisted of those receiving treatment for periodontitis problems were randomly assigned to rinse with either 20 mL of Listerine® or 20 mL of placebo as control rinse. Every subject was instructed to gargle using the rinse for 1 min. Microbial samples of environmental air and saliva were collected before and after the rinse. All samples were further analyzed for total plate counts to measure the microbial level. Rinsing using Listerine® showed significant reduction in the level of microbial load in saliva compared to the control mouthrinses. Analysis done at three defined distance intervals from the operating site showed the level of bioaerosol contamination was highest at distance nearest to the treatment point of 1 ft. Based on counts of cfu, there was higher presence of microbial contaminant in bioaerosols of the control-rinsed group compared to the test-rinsed group using Listerine®. Therefore, it can be concluded that rinsing using Listerine® was effective towards reducing the microorganisms in saliva and oral cavity in general.